Kinerja PPID (Pejabat Pengelola Informasi Publik Dan Dokumentasi) Dalam Menerapkan Keterbukaan Informasi Publik Di Lingkungan Pemerintahan Kota Probolinggo - Ferliana Ferliana; Mohammad Natsir (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2024)
Law of the Republic of Indonesia number 14 of 2008 concerning Public Information Disclosure indicates that state administration must be carried out in an open or transparent manner. The Administration of government must be able to create public trust in the government, one of which is by meeting the information needs of the community. The City Government of Probolinggo has committed to carrying out the mandate of the Law on Public Information Disclosure by making a policy of establishing a public information and Documentation Management Officer (PPID) consisting of Main PPID and Supporting PPID. Even though they have carried out their duties accordance with the mandate of the law, the Probolinggo City PPID is still experiencing several obstacles, one of which is the existence of information disputes submitted by information applicants. Therefore it is necessary to carry out research related to the performance of the Probolinggo City PPID in implementing Public Information Disclosure and examining the constraints faced. In this study using a qualitative descriptive approach. The results of this study indicate that the performance of PPID Probolinggo City in implementing Public Information Disclosure has been good. However, there are still a number of obstacles encountered, namely the lack of competent human resources in their fields and the lack of orderly administration in the preparation of DIP and the determination of exempted information that has not been completed with a consequential test document.